Case Report: Two Cases of Watershed Phenomenon in Mechanical Circulatory Support Devices: Computed Tomography Angiography Imaging and Literature Review - Du, Guiying; Zhang, Jiwang; Liu, Junbo; Fan, Lijuan (Frontiers in Cardiovascular Medicine, 2022)
Mechanical circulatory support (MCS) has become a processing technique used in end-stage heart failure (ESHF) because it can significantly improve survival and quality of life in patients with ESHF as either a transitional support therapy or a permanent replacement therapy before heart transplant. However, various potential complications associated with the use of MCS need to be taken into consideration, especially aortic root thrombus formation. It's critical to have an appropriate diagnosis of aortic root thrombus and "pseudo-thrombus" because the prognosis and treatment are different. Both "pseudo-thrombus" signs and aortic root thrombus formation can be characterized on computed tomography angiography(CTA). The CT manifestations of two patients who had MCS device implantation in our hospital (one with intra-aortic balloon pumps (IABP) + extracorporeal membrane oxygenators (ECMO), the other with left ventricular assist devices (LVAD)) were reported, and a literature review that recognized the sign of "pseudo-thrombus" in the aortic root was conducted.